O imagine a indicelui calității vieții din România şi urbanul mare românesc în context internațional - Stanciu, Mariana (Calitatea Vieții, 2018)
This study presents a point of view on how to conceptualize a domain of high relevance in social research, such as the quality of life. In this respect, we used the NUMBEO.com database. In this expected quality of life index refering to national levels and large cities might be taken into account as a broad comparative term of social interest. The base Numbeo.com uses as reference terms New York City’s analytical and synthetic life quality indicators (to which 100% relative value is attributed), such as the Quality of Life Index, the purchasing power index, the cost of living, the cost of house keeping, the time spent in traffic and other indices. The data of this study refers to July and January 2017. One of the conclusion of study is that Romania occupies a less favorable position in an international comparison. Also Bucharest offers to the population, at least in some areas, poor average quality of life, if we compare it with smaller Romanian cities